Economic Evaluation of Ready-to-use Injectable Medications by Pharmacy Department Compared with the Traditional System of Individual Preparation by Nurse - Noparatayaporn, Prapaporn; Thaweethamcharoen, Tanita; Laocharoenkeat, Apirom; Narkchuay, Panitta; Klinniyom, Anchalika; Nopmaneejumruslers, Cherdchai; Wangtawesap, Khemchat; Pitimana-aree, Siriporn; Sakiyalak, Darin (Siriraj Medical Journal, 2019)
Objective: To dispense medication in a form of ready to use (RTU) medication was recommended by the standards of Joint Commission International (JCI) and Standard Guidelines of Hospital Pharmacy for preventing the medication error. However, the cost and benefit were questionable. The costs may increase while benefits were unclear. Before making the implementation decision, the cost of investment and benefit between traditional (injectable medication is prepared by nurse) and RTU systems (injectable medication is prepared by pharmacy department) should be evaluated. Methods: This study compared the cost and benefit of injectable medication administration between the traditional system and the RTU system within a large academic hospital. The decision tree was designed to produce comparable data on the hospital’s perspective. The time horizon was 10 years thus all costs were discounted at 3% annually. Sensitivity analysis was performed to test the stability of the results. Results: The cost of investment at 10-year intervals of the RTU system was lower than the traditional system by about 18,710,160 baht. The benefit was decreased 19.32 full time equivalents (FTEs) of nurse when compared with the traditional system. The result showed that the five most sensitive variables were number of doses, mixing time per dose (prepared by nurse), space for production, salary and fringe benefits of pharmacists, and mixing time per dose (prepared by pharmacist). Conclusion: The RTU system saved 1,871,016 baht per year and 19.32 FTEs of nurse. Moreover, the RTU system enhanced the opportunity of nurses and pharmacists to play more professional role and promoted the efficient health care system.